Does refining an intervention based on participant feedback increase acceptability? An experimental approach - Chris Keyworth; Leah Quinlivan; Jessica Z. Leather; Rory C. O'Connor; Christopher J. Armitage (BMC, 2023)
Abstract Background Participant feedback is an important consideration for increasing intervention acceptability, yet whether incorporating such feedback actually improves acceptability is rarely tested. Purpose The present study describes a theory-based approach to assessing whether refining an intervention based on participant feedback increases acceptability. Methods Three hundred and ninety-three UK adults who had previously self-harmed were exposed to the same intervention at baseline and, six months later, were randomly allocated to receive either: (a) the same version of the intervention (control group), or (b) a version of the intervention that had been refined following participant feedback (experimental group). The main outcome measure was acceptability ratings for each of the seven domains specified in the Theoretical Framework of Acceptability (TFA). Results Mixed ANOVAs, with control versus experimental group as the between-participants factor and time (baseline versus follow-up) as the within participants factor showed no significant changes in acceptability. Conclusions The null effects reported here imply that participants found both the original and modified versions of the intervention equally acceptable, and that our process of refining an intervention based on participant feedback did not impact on acceptability. Nevertheless, we have operationalised a robust approach for examining whether participant feedback impacts on the acceptability of an intervention. Further research is required to understand better how participant feedback should be incorporated into the development of healthcare interventions.